(3GdLhGfH GdbGfhfjI ddMb ai GdfSjGf ai GdYGde GdQbei (B: s (3OQGSI ebGQfI (B/ s - (3eMeO CMeO YHOGdMejO GdSjOs; (3YHOGdgGOi ahRi GdYhVi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2021)
(3JJSe GdWHjYI GdHTQjI HchfgG eJZjQI h eJWhQI h eJLOOI HGSJeQGQ(B: (3h gh GdCeQ GdPi jLO GdeQA faSg ajg HMGd jQZH eYg ai EONGd HYV ef CLRGpA MjGpJg GdeGVjI (B- (3dG SjeG GdeTjfI efgG (B- (3ai Wi GdfSjGf(B: (3deG ai Pdc ef Uhf dMbg ai GdNUhUjI h GdcQGeI GdEfSGfjI h MeGjI dHjGfGJg GdTNUjI(B. (3h JHYG dPdc(B: (3XgQJ GdMGLI edMI Edi GdMb ai GdfSjGf(B: (3Pdc GdMb GdPi jNhd UGMHg oecfI GdSjWQI ef MjK GdReGf Ydi HjGfGJg GdTNUjI(B: (3HZjI MPagG Ch eMhgG YfOeG jQZH ai Pdc(B: (3dG SjeG h Cf GdJWhQGJ GdJcfhdhLjI GdeJYGbHI bO SGgeJ ai JgjFI HjFI JSeM HRjGOI cejGJ GdHjGfGJ GdJi jLQi JNRjfgG YHQ GdYGde GdQbei (B"(3YGde GdEfJQfJ(B": (3NGUI HGdfXQ Edi bdI JcdaI GdJNRjf ai Xd RjGOI bjeI GdHjGfGJ h JYOO hLhg GSJNOGeGJgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfis
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B421-449s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdeOfjs; (3GdHjGfGJ GdTNUjIs; (3GdMb ai GdfSjGf GdQbeis; (3GddGFMI GdChQhHjI GdYGeI dMeGjI GdHjGfGJs; (3GdHjGfGJ GdMSGSg s; (3GdMb ai GdNUhUjg s; (3Gdehba GdbVGFi ef GdMb ai GdfSjGf s; (3GdfWGb GdLZQGai ddMb ai GdfSjGfs; (3QO GdGYJHGQ s; (3GdbGfhf GdchjJi s; (3GdbGfhf GdeZQHi s; (3GdbGfhf GdJhfSjs; (3GdbGfhf GdLRGFQi s; (3GdbGfhf GdeUQjs; (3GdeSFhdjg GdeOfjg Yf GfJgGc GdMb ai GdfSjGf s; (3GdMb ai GdJUMjM hGdeMhs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs